The Ethical Case for Affirmative Action - Burns, Prue (Journal of business ethics, 2008)
Affirmative action has been a particularly contentious policy issue that has polarised contributions to the debate. Over recent times in most western countries, support for affirmative action has, however, been largely snuffed out or beaten into retreat and replaced by the concept of ‹diversity management’. Thus, any contemporary study that examines the development of affirmative action would suggest that its opponents have won the battle. Nonetheless, this article argues that because the battle has been won on dubious ethical grounds it is important that we do not allow affirmative action to sink unnoticed. This article explores and challenges the ethical and philosophical underpinnings of opponents’ views and finds their cases against affirmative action are not ethically sound. The article concludes there are strong ethical grounds for those organisations which seek to do well, to reassert affirmative action programmes in the global efforts to eradicate systemic discrimination and disadvantage.